Self-esteem, assertiveness and resilience in adolescents institutionalized - Zélia Caçador Anastácio (INFAD, 2016)
The institutionalization of children and adolescents has been an increasingly visible problem in modern society. Unfavourable socio-economic conditions have been joining the behavior problems and school absenteeism. When the family fails in its competence for education, social security or the Court withdraws the child or adolescent to a host institution.